KERAGAMAN JAMUR PATOGEN PADA SERANGGA PENGUNJUNG TANAMAN PISANG DI PERKEBUNAN PISANG UNIVERSITAS TEUKU UMAR - Chairudin Chairudin; Sumeinika Fitria Lizmah (Universitas Teuku Umar, 2021)
The presence of plant visiting insects can occur a infection of disease on banana plants caused by fungi pathogenic, therefore information of types of insects vector and fungal pathogens carried is important to know. The aim of this study is to detect potential insects as vectors and types of pathogenic fungi on banana plants at University Farm, Teuku Umar University. The method used was purposive sampling by collecting insects, then continued with insect identification, isolation of pathogenic fungi, and characterization isolates of pathogenic fungal. The results showed that there were three potential vectors as insects on banana plants at UTU University Farm, namely Tachypeza sp., Bactrocera sp., And Erionota trax. The types of pathogenic fungi carried by the three vector insects are the fungus Curvularia lunata , Mycosphaerella and Fusarium oxysporum. Keywords: Banana, insects vector, plant visiting insects, fungi pathogenic, isolation